Estudios Limnológicos en la Cuenca del Riachuelo (Corrientes, Argentina). I. Poblaciones de peces en ambientes Leniticos y loticos - Bonetto, Argentino A.; Roldan, Dante; Oliver, M. Esteban (Ecosur, 2024)
The present paper deals with the structural and distributional characteristics of the fish population of the extended complex of pools, swamps and marshes belonging to the basin of the Riachuelo River, a small tributary of the Paraná River, near the confluence of the Paraguay River, in the N.W. of the Corrientes Province. Durine the years 1974-1977, the studies were performed in several samplings stations: 7 along the Riachuelo River and 31 in differentic waterbodies of its basin. In the whole area were registered 124 species of fishes belonging to 81 genera, 24 families and 11 orders, recording the greatest diversity in the Riachuelo river, where prevail typical fishes of lotic waters. In the pools, swamps and marshes of its basin were registered 73 species, from which 26 were absent in the Riachuelo’s waters. Only one typical migratory fish: Prochilodus platensis, was somewhat frequent. The distributional mechanisms resulting from the rain floods are analized, as well as the integration of new populations, the trophic relations, the contributions of these bodies to the bioproductivity of the Riachuelo’s waters, and the possibilities offered by them to the development of the regional pisciculture.